Underutilization of instructional materials for teaching and learning of Chemistry in Nigerian secondary schools: Ohafia Education Zone, Abia State's Example. - Ngozi Obiyo (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2019)
This study investigated the factors associated with underutilization of instructional materials for teaching and learning of Chemistry in Nigeria. A survey research design was adopted for the study. The study population comprised 86 Chemistry teachers and 1,180 Senior Secondary 2 (SS2) Chemistry students including those with special needs in the 86 public secondary schools in Ohafia Education Zone, Abia State in southeast geopolitical zone of Nigeria. The sample size was 456 respondents of 57 Chemistry teachers and 399 SS 2 Chemistry students selected through multi-stage sampling procedure. The data collection was by questionnaire and Cronbach Alpha was applied in computing the reliability estimate of 0.97. The findings indicated that the inability of teachers to improvise and their lack of manipulative skills, among others, are factors militating against the utilization of instructional materials. The researchers recommended the necessity for adequate provision of instructional materials in the schools and for teachers to ensure that these materials are effectively utilized. Students with special needs should be catered for based on their individualized education program as stipulated by the National Policy on Education in inclusive settings.